Transformasi Pendidikan Agama Islam Melalui Artificial Intelligent (AI): Upaya Meningkatkan Kemampuan Berpikir Kritis Mahasiswa - Sodikin, Sodikin (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2024)
Islamic education plays a major role in preserving the values of human life. Although humanity has made a lot of progress, especially in the digital age that is changing the order of life, Islamic religious education must remain in control of that goal. In addition, the existence of Arfificial Intelligent (AI) technology has also reduced the role of humans. Therefore, human critical thinking must be improved by using AI technology. This research aims to explore higher education in developing students' critical thinking skills through the use of artificial intelligence technology. The approach used in this study is a qualitative approach with the type of case study. Data collection techniques are carried out by observation, interviews and documentation. The main informants in this study are lecturers and students of Darullughah Wadda'wah International Islamic University. Data analysis was carried out through three categories, namely condensation, display and verification. To corroborate the findings of the research results, the researcher conducted triangulation, both data triangulation and source triangulation. The results of this study show that AI technology is very effective in developing students to think critically. AI can stimulate students' critical thinking based on AI considerations. Their limitations in telling the idea of knowledge will be overcome with this AI technology. The integration of artificial intelligence in Islamic education has the potential to revolutionize the way students learn and engage in their studies. Using AI technology to personalize the learning experience, educators can meet individual needs and interests, which ultimately improves students' critical thinking skills. Following up on these findings, the improvement of students' critical thinking skills through the use of AI technology must be further optimized through the design of learning plans, learning resources, and AI-based learning assessments.